2018
DOI: 10.1212/wnl.0000000000005166
|View full text |Cite
|
Sign up to set email alerts
|

CSF tau and β-amyloid predict cerebral synucleinopathy in autopsied Lewy body disorders

Abstract: Higher antemortem CSF t-tau/Aβ and lower Aβ levels are predictive of increasing cerebral AD and SYN pathology. These biomarkers may identify patients with LBD vulnerable to cortical SYN pathology who may benefit from both SYN and AD-targeted disease-modifying therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
63
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 42 publications
7
63
0
Order By: Relevance
“…An analysis of the DATATOP (Deprenyl And Tocopherol Antioxidant Therapy of Parkinson's) trial found that higher levels of CSF tau may be related to faster motor progression . Whereas postmortem validation studies in LBD are rare, CSF measurements of tau and Aβ1‐42 relate to the severity of AD pathology in LBD, as previously observed in AD . Interestingly, low CSF Aβ1‐42 may also relate to neocortical distribution of SYN pathology .…”
Section: In Vivo Biomarker Associations With Patient Subtypesmentioning
confidence: 86%
See 4 more Smart Citations
“…An analysis of the DATATOP (Deprenyl And Tocopherol Antioxidant Therapy of Parkinson's) trial found that higher levels of CSF tau may be related to faster motor progression . Whereas postmortem validation studies in LBD are rare, CSF measurements of tau and Aβ1‐42 relate to the severity of AD pathology in LBD, as previously observed in AD . Interestingly, low CSF Aβ1‐42 may also relate to neocortical distribution of SYN pathology .…”
Section: In Vivo Biomarker Associations With Patient Subtypesmentioning
confidence: 86%
“…Whereas postmortem validation studies in LBD are rare, CSF measurements of tau and Aβ1‐42 relate to the severity of AD pathology in LBD, as previously observed in AD . Interestingly, low CSF Aβ1‐42 may also relate to neocortical distribution of SYN pathology . Further work is needed to elucidate the relationship between ante mortem AD CSF biomarkers and underlying neuropathology and to continue to collect longitudinal data on CSF measurements in well‐characterized cohorts .…”
Section: In Vivo Biomarker Associations With Patient Subtypesmentioning
confidence: 97%
See 3 more Smart Citations